2020
DOI: 10.5433/1679-0359.2020v41n1p283
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of sheep to three salinity levels in different environments

Abstract: The objective of this study is to evaluate physiological parameters and the adaptability of Santa Inês sheep to two climatic conditions 25ºC (within the thermal comfort zone [TCZ) and 32ºC (above the TCZ) and three salinity levels (2.0, 4.0, and 8.0 dS m-1). The study was developed in a climatic chamber using 36 uncastrated male sheep. The experimental design was completely randomized with a 2 ´ 3 factorial scheme composed of two temperatures, three water salinity levels, and six repetitions. The physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Thus, we observed that the decreased consumption of ethereal extract by goats subjected to a higher temperature can be related to the lower need for production and dissipation of body heat (Wolp et al, 2012). Animals kept in a high temperature environment need to eliminate latent body heat, such as respiration, peripheral vasodilation, and sweating (Furtado et al, 2020). Ribeiro et al (2018) mention that, regardless of breed, environmental variables trigger physiological and behavioral changes in goats to maintain their homeothermia.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, we observed that the decreased consumption of ethereal extract by goats subjected to a higher temperature can be related to the lower need for production and dissipation of body heat (Wolp et al, 2012). Animals kept in a high temperature environment need to eliminate latent body heat, such as respiration, peripheral vasodilation, and sweating (Furtado et al, 2020). Ribeiro et al (2018) mention that, regardless of breed, environmental variables trigger physiological and behavioral changes in goats to maintain their homeothermia.…”
Section: Discussionmentioning
confidence: 94%
“…One of the reasons for the increase in this excretion is that the animal organism does not store sodium and its reserves are limited, so excess sodium is quickly excreted in the urine. Potassium is closely related to sodium, and sodium intake in the body is negatively correlated with potassium excretion (Dewhurst et al, 1968), the lower the Na intake, the greater the K excretion. But this did not occur in the present study may be due to the amount of magnesium excreted being close to potassium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation